2012
DOI: 10.1055/s-0032-1329811
|View full text |Cite
|
Sign up to set email alerts
|

Serum Level of CC-Chemokine Ligand 18 is Increased in Patients with Non-small-cell Lung Cancer and Correlates with Survival Time in Adenocarcinomas

Abstract: CC-chemokine ligand18 (CCL18) ismainly expressed by alternativelyactivated macrophages and DCs and plays an important role in lung fibrosis, arthritis and other diseases. Here CCL18 was measured in sera of 31 healthy volunteers and 170 patients with lung cancer and correlatedthese data with histology, tumor stage and clinicalparameters. Mean CCL18 serum levelofthe patients with non-small-cell lung cancer was 150(857) ng/ml vs. 32(61) ng/ml in the healthy control group. Patient groups differ significantly accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…We have previously demonstrated that CCL18 binds to Nir1 and plays a critical role in inducing epithelial‐mesenchymal transition (EMT) of breast cancer . Recently, it is reported that serum level of CCL18 is increased in NSCLC and correlates with survival time in adenocarcinomas . By coincidence, our pilot study showed that CCL18 can promote the migration and invasion of lung cancer cells.…”
Section: Introductionmentioning
confidence: 54%
“…We have previously demonstrated that CCL18 binds to Nir1 and plays a critical role in inducing epithelial‐mesenchymal transition (EMT) of breast cancer . Recently, it is reported that serum level of CCL18 is increased in NSCLC and correlates with survival time in adenocarcinomas . By coincidence, our pilot study showed that CCL18 can promote the migration and invasion of lung cancer cells.…”
Section: Introductionmentioning
confidence: 54%
“…Previous studies on lung cancer demonstrated that the accumulation of CCL18-positive TAMs in pathological sections was associated with a poor prognostic outcome (22). Correspondingly, high serum concentrations of CCL18 in lung adenocarcinoma were also associated with an unfavorable prognosis (23).…”
Section: Discussionmentioning
confidence: 97%
“…Overexpression of AQP1 has been found to be associated with a poor survival in lung adenocarcinoma (Yun et al). Lung cancer patients with a higher serum CCL18 level have a shorter survival (Pl önes et al).…”
Section: Case Studymentioning
confidence: 99%